Prilagoditev in psihometrična validacija Lestvice profesionalnih kompetenc medicinskih sester v izrednih razmerah v času epidemije SARS-CoV-2 (COVID-19) v Sloveniji - Prosen, Mirko (Obzornik zdravstvene nege, 2020)
Introduction: In order to deal with the changed roles successfully, confidently and effectively, and to be able to ensure appropriate assistance to those affected during the state of emergency, nurses should be properly trained and prepared. The purpose of the study was to translate, adapt, and evaluate the psychometric properties of the Disaster Nursing Core Competencies Scale (DNCC-Scale). Methods: A quantitative methodological research design was used. The scale was tested on a convenience sample of 118 nurses. In addition to content compliance, internal consistency, stability and correlation of variables and factor structure were also evaluated in the three-phase process of adaptation and validation. Results: Factor analysis provided a three-factor model with the first factor Core Competencies of Nurses in Emergencies explaining 36.53% of the total variance. The results also show a very high correlation between factors (p < 0.001) and high reliability of the overall scale (Cronbach % = 0.937). Discussion and conclusion: The results have confirmed that the Slovenian version of the DNCC-Scale is a valid and reliable measuring instrument. In the absence of appropriate measurement instruments, it enables an identification of the core competencies of nurses in disaster management and some other circumstances of their roles. The findings also suggest the need for the implementation of some changes in nursing study programs and for more focused studies on those groups in nursing who are expected to encounter disaster events more frequently.
Keywords: civil protection; civilna zaščita; coronavirus disease; disaster relief; javne nesreče; javno zdravje; koronavirusna bolezen; mass accident; nursing; public health; reševanje; zdravstvena nega